Path-dependency theory in a post-conflict state: the case of Fiji. Issue 3 (13th December 2021) - Loga, Patricia; Cardow, Andrew; Asquith, Andy
Abstract : Purpose: Violent geo-political conflicts are on the rise across the globe, particularly within fragile states. Using path-dependency theory, this paper aims to explore Fiji in the context of its public administrative history examining the legacies of history that have contributed to its ongoing conflicts. Design/methodology/approach: An archival document analysis along with a theoretical thematic analysis was used to collect and assess data. Themes were identified that explain how and when the conflict became path-dependent. Findings: Analysing conflict as path-dependent demonstrates how indirect rule while Fiji was under colonial rule, and the short time it has taken for the nation to transition from a colony to an independent State contributed to the eruption of conflicts in Fiji. Originality/value: The research makes two key contributions, namely, it develops a theoretical understanding of conflict using path-dependency theory and it uncovers legacies of colonialism that have shaped conflict in Fiji.